Synthesis, Structural Studies, and Magnetic Properties of a New Mixed-Valence Diphosphate: Zn2+5Fe3+2(P2O7)4 - Lamsaf, H. (2019)
A new mixed-valence diphosphate, Zn2+5Fe3+2(P2O7)4, was synthesized from FeII5FeIII2(P2O7)4 via the “solid way” route, by substitution of FeII by ZnII. The obtained X-ray data confirmed the crystallization of the compound in the C2221 symmetry space group (orthorhombic). Magnetic measurements were performed showing that, at room temperature, the compound is paramagnetic and that the Néel temperature is 15.44(20) K. The compound was also investigated by infrared and Raman spectroscopies, in particular to characterize the (P2O7)4− and M–O vibrations.